OBTENÇÃO, CARACTERIZAÇÃO, CITOTOXICIDADE E FARMACOCINÉTICA DE NANOEMULSÃO REVESTIDA COM QUITOSANA CONTENDO LUTEOLINA VISANDO SUA ADMINISTRAÇÃO INTRANASAL PARA O TRATAMENTO DE NEUROBLASTOMAS - DIEDRICH, CAMILA (2022)
Luteolin (LUT) is a flavonoid found in several edible and medicinal plants and is recognized for its biological activities, such as antioxidant, anti-inflammatory, neuroprotective, and antitumor. However, the limited water solubility of LUT leads to low bioavailability, decreasing its absorption when administered orally. Nanoencapsulation improves solubility and bioavailability of bioactive compounds. Nanoemulsions (NE) are characterized by the dispersion of two immiscible phases stabilized by surfactants. Among the advantages of using NE in the encapsulation of bioactive compounds, are the prolonged release, biodegradability, and increased permeability through the membranes. In this work, luteolin-containing NE coated with chitosan (NECh-LUT) was developed to improve LUT permeability aiming intranasal application for brain delivery. The NECh-LUT was obtained by the ultrasound cavitation method and showed a mean diameter of 67.5 nm, a surface charge of +12.8 mV, and encapsulation efficiency of 85.49%. Transmission electron microscopy showed spherical shape and size homogeneity. The Small-angle X-ray scattering technique confirmed the bimodal characteristic of NECh-LUT, while the differential scanning microcalorimetry showed endothermic events above 80 ºC attributed to the formulation destabilization processes. The rheological analysis provided the verification of the Newtonian behavior of the NECh-LUT, and the Fourier-transform infrared spectroscopy showed spectra with characteristic bands of the components of the formulation. The NECh-LUT was stable when stored at room temperature for up to 30 days. In vitro mucoadhesion and permeability studies through the nasal mucosa demonstrated the ability of NECh-LUT to cross membranes due to the mucoadhesive capacity of the formulation, which is crucial for intranasal administration. In vitro release assay showed the prolonged release of LUT from NECh-LUT, occurring through the process of diffusion and degradation of spherical shaped lipid matrices. The cytotoxicity assay against neuroblastoma cells showed greater efficiency of NECh-LUT compared to the free drug. The pharmacokinetic study was developed following oral and intranasal administration of NECh-LUT and free drug and the pharmacokinetic parameters were evaluated in plasma, brain and lung. The nanoencapsulation provided an increase in the bioavailability of LUT in brain and lung tissues when administered by both routes. Finally, the intranasal route ensured targeting efficiency and targeting potential of 540.90% and 80.39%, respectively. The results obtained indicate that the encapsulation of LUT into NE coated with Ch ensured increased bioavailability of the drug, offering an alternative for the treatment of neuroblastomas.